2014
DOI: 10.4049/jimmunol.1303203
|View full text |Cite
|
Sign up to set email alerts
|

Functional Avidity–Driven Activation-Induced Cell Death Shapes CTL Immunodominance

Abstract: Immunodominance is a complex phenomenon that relies on a mere numerical concept, while being potentially influenced at every step of the immune response. We investigated the mechanisms leading to the establishment of CTL immunodominance in a retroviral model and found that the previously defined subdominant Env-specific CD8+ T cells are endowed with an unexpectedly higher functional avidity than is the immunodominant Gag-recognizing counterpart. This high avidity, along with the Env Ag overload, results in a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 42 publications
(44 reference statements)
0
4
0
Order By: Relevance
“…The idea of "reverse immunoediting" firstly stemmed from the analysis of immunodominance (ID) in a retrovirus-induced tumor model [2]. In this study, we observed an unexpected immunodominance hierarchy in favor of lower avidity responding T cells ( Fig.…”
Section: How Viruses Can Sculpture the Immune Responsementioning
confidence: 65%
“…The idea of "reverse immunoediting" firstly stemmed from the analysis of immunodominance (ID) in a retrovirus-induced tumor model [2]. In this study, we observed an unexpected immunodominance hierarchy in favor of lower avidity responding T cells ( Fig.…”
Section: How Viruses Can Sculpture the Immune Responsementioning
confidence: 65%
“…The APCs will process and present this de novo expressed gp70 via the endogenous route, and, in this context, immunodominant viral antigen epitopes will be presented by a large number of APCs resulting in the induction of anergy or clonal deletion of most gp70specific CD8 + T cells, probably through activation-induced exhaustion of the majority of high affinity TCR T cells. 48 The residual surviving gp70-AH1-specific T cells, detected by ELISPOT and tetramer staining (Fig. 8a,b), are probably low-affinity clones, likely to be overcome during immune response amplification by different and more Sp6-specific tumour antigens.…”
Section: Discussionmentioning
confidence: 96%
“…A synergic stimulus for gp70 expression may be elicited by virus particles discharged by the CTL-lysed cells that may superinfect resident APCs. The APCs will process and present this de novo expressed gp70 via the endogenous route, and, in this context, immunodominant viral antigen epitopes will be presented by a large number of APCs resulting in the induction of anergy or clonal deletion of most gp70-specific CD8 + T cells, probably through activation-induced exhaustion of the majority of high affinity TCR T cells 48. The residual surviving gp70-AH1-specific T cells, detected by ELISPOT and tetramer staining (Fig 8a,b…”
Section: Discussionmentioning
confidence: 99%
“…The tetramer staining intensity reflecting TCR avidity has been described as a marker for functional T cells. In detail, high tetramer binding T cells have been shown to be associated with high levels of cytotoxicity (16), high sensitivity to activation-induced cell death (17,18), senescence (19), and exhaustion (20,21). In contrast, low tetramer binding CMV T EMRA CTLs have been shown to accumulate in elderly CMV-seropositive individuals and to be associated with low effector function (22).…”
mentioning
confidence: 99%